Influência dos métodos de estimação das funções de proteção anti-ilhamento passivas considerando requisitos de suportabilidade - Friedemann, Daniel Filipe (2021)
The power capacity growth of distributed energy resources (DERs), combined with the occurrence of collapses due to incorrect disconnection of these generations, has brought to debate the security and dependability of the electric power system in the presence of large power capacity of DERs. With this concern, the ride-through requirements set limits for which the DERs shall ride-through the system excursions without tripping, as not to contribute to abnormal system occurrences. Besides, passive anti-islanding methods use measured system quantities to define if unintentional islanding has occurred. The more sensitive the anti-islanding protection settings are, the greater are the chances of incorrect disconnection of DERs due to abnormal system occurences. In this aspect, this research approaches different estimation methods for the most used passive anti-islanding function techniques: under/overfrequency (ANSI 81U/O), under/overvoltage (ANSI 27/59), rate of change of frequency (ANSI 81R), and vector surge (ANSI 78VS) and how the estimation methods of frequency, voltage, rate of change of frequency (RoCoF) and vector surge might impact in the compliance of the ride-through requirements. The research is achieved by simulation of known signals applied to the estimation models, simulation of islandings, short-circuits, and connection/disconnection of large power loads in a distribution system based on IEEE 34-bus. Furthermore, signals of occurrences of the Brazilian transmission system are also applied to the estimation methods programmed in MODELS language from the Alternative Transients Program. The achieved results show that the estimation methods can impact the performance of the ride-through requirements, depending on the employed estimation method and specific parameters of each quantity: for the voltage, the frequency tracking; for the frequency, the estimation method, and the average filter window size; for the RoCoF, the average filter window size; for the vector surge, the current period estimation method and the reference period estimation method. Lastly, this research gives an important contribution developing an equivalent equation for the vector surge estimation, resulting in a tool for analysis of the vector surge behavior since it is only necessary a frequency signal of the event and the knowledge of the vector surge estimation method.